Proyecto de Factibilidad para la Producción de Miel de Abeja en la Parroquia Bellavista del Cantón Espíndola, y su Comercialización en la Ciudad de Loja - Tamayo Cordero, Diana Mariline (2015)
This paper develops the interest and increase the families of the city of Loja, to consume natural and healthy products, mainly due to the problems of health and nutrition that the pace of modern life brings to humans. Within these products honey is an excellent alternative for its many beneficial properties, however, the demand is much greater than supply because beekeepers are unaware of the different methods used for production, collection and preservation of this product. This paper's main purpose is to demonstrate the feasibility of the production and marketing of honey. The project is located in the Bellavista parish Espindola canton province of Loja. The methodology that was supported this research was in the deductive, inductive methods; supported field research techniques such as direct observation, survey and interview. To carry out field research, target market first and then the sample size of the families of the city of Loja and proceed with the collection of information was determined. The results obtained after analyzing and interpreting information are favorable in which the following was determined: the consumption of honey is of 76,90%, consumption of honey is of 92,49, the frequency of consumption monthly with 70,48%, whichever is more consumed monthly 300g pack with 46,13%, where more honey you buy at the mall with 43,24% and in health food stores 32,43 %, the 96,31% would be willing to buy the product of the new production unit, 81,55% prefer the glass container, the 52,11% valued more quality when buying them and to 36,27% You would like to know the product on TV. “PROYECTO DE FACTIBILIDAD PARA LA PRODUCCIÓN DE MIEL DE ABEJA EN LA PARROQUIA BELLAVISTA DEL CANTON ESPINDOLA, Y SU COMERCIALIZACIÓN EN LA CIUDAD LOJA” Autora : Diana Tamayo Página 6 According to the results it was determined that the potential demand is 76,90%, the actual 92,49% 96,31% effective real and unmet 98,59%. It was considered that the product will be released under the brand GRAPICOLA; and the product as "MIELAB" in glass bottles to provide a longer product life. To determine the capacity utilization of project performance technology component that determined the level of production and human resources in relation to the unmet demand to be covered and 100% of the capacity is used to produce annual installed considered 13.200.000gr ; 44.000 units 300g occur. The company will be located in the parish of Bellavista Espindola canton of Loja province, with an investment of $ 80.577,92 and working capital is $ 38.787,92. The net present value is $ 68.589,09 IRR 37,68%; Benefit Cost Ratio for every dollar invested the company earns $ 0,97 cents; the Capital Recovery Period is 3 years, 10 months and 24 days. And finally the sensitivity analysis indicates that the project supports increased costs 53,73% .And the sensitivity analysis with decrease in revenues of 27% by which the project is feasible. Therefore it is concluded that the project is feasible, so that there is a high level of acceptance of the product by the target market, and the availability of purchase and consume this product. To end the implementation of this company is recommended, because it is economically profitable according to the results.